Transatlantic Trade and Investment Partnership (TTIP) and the Global and Regional Security System - Czarny, Elżbieta; Folfas, Paweł; Menkes, Marcin (Studia Oeconomica Posnaniensia, 2017)
In the paper we analyse the Transatlantic Trade and Investment Partnership (TTIP) indicating its possible impact on global and regional security systems. We stress the specific character of this agreement. It comes with the parties' particular characteristics. We examine changes in the positions of the United States and the European Union in the world economy and international trade in the years 1995-2013 (in trade in services and FDI flows, the unavailability of data forced us to analyse a shorter period). We illustrate them with changes of the GDP as well as of shares in the international export of goods and services. Based on values of their mutual trade and FDI flows we present the interconnection of their economies. The point of reference is the global economy and the BRIC countries (Brazil, Russia, India, and China). In our opinion closer economic co-operation between the EU and the U.S. is a supplement of their political alliance. Moreover, it will allow both parties to increase their impact on the global economic order including the non-discriminatory liberalization of economic cooperation in the framework of the WTO.